2016
DOI: 10.1016/j.sjbs.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural effects on gill tissues induced in red tilapia Oreochromis sp. by a waterborne lead exposure

Abstract: Experiments on hybrid red tilapia Oreochromis sp. were conducted to assess histopathological effects induced in gill tissues of 96 h exposure to waterborne lead (5.5 mg/L). These tissues were investigated by light and scanning electron microscopy. Results showed that structural design of gill tissues was noticeably disrupted. Major symptoms were changes of epithelial cells, fusion in adjacent secondary lamellae, hypertrophy and hyperplasia of chloride cells and coagulate necrosis in pavement cells with disappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 26 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…Following feeding, the remaining pellets were removed from the aquarium (36.5 cm × 25 cm × 26 cm glass aquarium) using a scoop net and dried, and the weights were determined in order to ascertain the actual weight of the feed consumed by the fish in each aquarium every day. Feeding was stopped 24 h prior to the commencement of the experiment [ 37 ]. Fish (ten fish per dosage, five male and female per dosage) were subjected to five glyphosate dosages (0, 25, 50, 100, and 150 mg/L) for 49 days.…”
Section: Methodsmentioning
confidence: 99%
“…Following feeding, the remaining pellets were removed from the aquarium (36.5 cm × 25 cm × 26 cm glass aquarium) using a scoop net and dried, and the weights were determined in order to ascertain the actual weight of the feed consumed by the fish in each aquarium every day. Feeding was stopped 24 h prior to the commencement of the experiment [ 37 ]. Fish (ten fish per dosage, five male and female per dosage) were subjected to five glyphosate dosages (0, 25, 50, 100, and 150 mg/L) for 49 days.…”
Section: Methodsmentioning
confidence: 99%
“…Lead (Pb), a widely deposited environmental toxicant, is known to impact the health status of exposed fish (Kennedy, ), including modulation of their immune functions (Paul et al, ). There are several previous studies which reported lead (Pb) LC 50 in O. niloticus (200 mg/L Zainuddin, Putranto, Irawan, & Soegianto, ; 11 mg/L Aldoghachi, Azirun, Yusoff, & Ashraf, ; 155 mg/L Said, Kairy, Shalaby, & Ismail, and 182.32 mg/L Lamchumchang et al, ). The current study revealed that exposure of O. niloticus to lead (20.2 mg/L) resulted in significant reduction in some innate immune functions including serum lysozyme activity, serum killing activity and nitric oxide production, suggesting that Pb may suppress the immune defence of O. niloticus against this existing stressor, and so may contribute to fish disease or death.…”
Section: Discussionmentioning
confidence: 97%
“…As already discussed, the capacity for active ion transport at the gills has been linked to the fractional surface area or the proportion of the total gill surface area occupied by the MRCs (Goss et al, 1992;Bindon et al, 1994;Chang et al, 2001). The MRC fractional surface area is well known to be actively regulated by fish in response to various stressors via changes in the density of MRCs (Pandey et al, 2008;Paulino et al, 2012;Pereira et al, 2013), altering individual apical surface area folding or flattening of microridges in the apical membrane (Laurent et al, 1995;Matey et al, 2008;Aldoghachi et al, 2016), and exposure of MRCs to water (Rind et al, 2017;Carmo et al, 2018). The latter is modified by the migration of MRCs within the filament epithelium (e.g., from deeper cell layers to the surface; Carmo et al, 2018) and by neighboring pavement cells shifting or expanding to cover or uncover MRCs (Laurent et al, 1995;Baker et al, 2009).…”
Section: Gill Remodeling In Response To Ocean Acidificationmentioning
confidence: 99%